PENGARUH KOMPENSASI, KEPEMIMPINAN ORGANISASI DAN WORK LIFE BALANCE TERHADAP KEPUASAN KERJA KARYAWAN PT. AGRI ANDALAS KABUPATEN SELUMA - Ulma, Ilvia Hafifah Ulma; Ratnawili, Ratnawili (UM. Bengkulu, 2025)
This study aims to determine the influence of Compensation, Leadership, and Work-Life Balance on Employee Job Satisfaction at PT. Agri Andalas, Seluma Regency. The respondents of this study were 100 permanent employees working at PT. Agri Andalas, Seluma Regency. The sampling technique used in this study was purposive sampling. Data analysis technique used multiple linear regression analysis, coefficient of determination, and hypothesis testing. Furthermore, compensation, leadership, and work-life balance simultaneously or together significantly influence job satisfaction at PT. Agri Andalas, Seluma Regency. Compensation, leadership, and work-life balance individually or separately influence job satisfaction. Leadership significantly influences job satisfaction. And work-life balance significantly influences job satisfaction.Keywords: Compensation, leadership, work-life Balance, job satisfaction